Dental robotics: a groundbreaking technology with disruptive potential – review article - Wafa Idrees; Rizwan Khalil; Leelan Kanwal; Mubassar Fida; Rashna Hoshang Sukhia (Journal of the Pakistan Medical Association, 2024)
Dental Robotics represent a groundbreaking technological frontier with the potential to disrupt traditional paradigms in oral healthcare. This abstract explores the transformative impact of robotic applications in dentistry, focussing on precision, reproducibility, and reliability. A comprehensive search was conducted on the PubMed database, Dental and Oral Science, and CINAHL to identify pertinent studies exploring the implications of robotics in dentistry. Studies incorporated in this analysis highlighted the significance of broadening the research scope beyond implantology. This review underscores the importance of integrating robotic dentistry into educational frameworks and advancing technological preparedness. As we navigate these challenges, the abstract underscores the pivotal role of robotic dentistry in shaping the future of oral healthcare. Continues...